BRCA mutation carriers' perception about benefits and risks associated with combined hormonal contraceptives use. (2nd November 2022) - Grandi, Giovanni; Monari, Francesca; Boggio Sola, Valentina; Cortesi, Laura; Toss, Angela; del Savio, Maria Chiara; Melotti, Chiara; Centurioni, Maria Grazia; Gustavino, Claudio; Varesco, Liliana; Facchinetti, Fabio; Barra, Fabio
Abstract: Objective: To evaluate the actual perceptions about combined hormonal contraceptives (CHCs) use in BRCA mutation carriers in comparison to women from the general population. Methods: This was a cross-sectional, observational study involving two Italian referral centres for hereditary cancers. An identical questionnaire investigating how CHC use could affect the risk of developing some types of cancer, specific diseases, and symptoms was administered to 85 BRCA mutation carriers and 85 healthy women without this genetic mutation (control group). Women's perceptions were evaluated using specific questions and Likert scales (−5 to +5). Results: Perceptions about the effects of CHC use on developing specific diseases and symptoms did not differ between BRCA mutation carriers and controls. Conversely, the protective effects of CHC use on colorectal ( p  = .02), uterine body ( p  = .01) and ovarian ( p  = .01) cancers were unknown by BRCA mutation carriers. Moreover, BRCA mutation carriers recognised the association between CHC use and a higher risk of breast ( p  = .0008) and uterine cervix cancer ( p  = .007). Conclusions: Investing time and effort in transmitting the correct key messages about oncological risk related to CHC use could potentially increase their use in BRCA mutation carriers.